A first look at the biodiversity of Loricifera in the southern Gulf of Mexico - Neves, Ricardo Cardoso; Kristensen, Reinhardt Møbjerg; Rocha-Olivares, Axayacatl; Rivas, Gerardo (Frontiers in Marine Science, 2022)
Loricifera is a group of marine, meiobenthic invertebrates of microscopic size that are found worldwide. The Loriciferan fauna of the Southern Gulf of Mexico (SGM) remains unknown. In the present study we report on the first exploration of the Loriciferans from the SGM, which is a strategic area for oil exploitation. The Loriciferan specimens were collected during deep-sea cruises XIXIMI-4 (August-September 2015) and XIXIMI-6 (August 2017), in which six out of 22 stations yielded specimens of Loricifera. A total of six specimens were found (although one of them was lost), namely two adults and four larval stages. Preliminary analyses based on the peculiarity of their morphological features indicate that the specimens include representatives of new species of Pliciloricus and Rugiloricus, an undescribed genus of Pliciloricidae and, possibly, an undescribed genus of Nanaloricidae. None of the specimens found could be assigned to previously described species. Since all specimens are either intermediate life cycle stages or poorly preserved, only a short description based on their morphological traits is provided here. Our findings are discussed from a comparative perspective with known Loriciferan species.